Controversial association between polycystic ovary syndrome and breast cancer. (December 2019) - Carvalho, Maria João; Subtil, Simone; Rodrigues, Ângela; Oliveira, Joana; Figueiredo-Dias, Margarida
Abstract: Polycystic ovary syndrome (PCOS) risk factors overlap with breast cancer, and the hormonal profile may be implicated in breast cancer pathogenesis. This study aims to report a literature review considering epidemiological and molecular mechanisms that correlate PCOS and breast cancer, as well as the influence of PCOS treatment on the incidence of breast cancer. Epidemiological studies failed to adjust potential variables that affect the risk and have thus provided inconclusive results. Molecular effects of androgenic pathways in breast cancer have been studied and androgens seem to have an inhibitory effect on mammary epithelial proliferation. However, increased bioavailable androgens were associated with recurrence of breast cancer due to conversion to oestrogens. Sex hormone-binding globulin has a role in hormone-dependent cancers and can be considered a marker for PCOS; a gene profile has already been linked to breast cancer risk in these patients. PCOS medical treatment is a promising tool for stratifying breast cancer risk due to the metabolic influence and hormonal environment. Clinical reports are inconsistent, emphasizing the need for further studies with a prospective design. In the future, the role of pharmacological interventions in PCOS will increase knowledge and awareness of breast cancer pathogenesis and will help to refine breast cancer risk stratification.